Institutional and Strategic Influences on IT Architecture Decisions: comparative case studies in Brazilian companies - Hsing, Chen Wen; Souza, Cesar Alexandre (Review of Business Management, 2013)
The aim of this paper is to examine the influences on IT architecture decisions by viewing it through the lens of Institutional Theory and of Strategic Choice Theory, using the comparative case studies. Institutional influence can be the result of an external action or of something internal within the organizational, whereas strategic influence is related to the voluntary behavior of managers. The case of a large-scale company, where there is extensive internal policy formalization, was compared to a midsize company with a less mature architecture level. In spite of their differences as to the use of IT architecture, similar findings appeared in both organizations concerning these two influences. Both types of influence act together: the strategic type was most mentioned during interviews, whereas the institutional type appeared in decisions related to innovation and risks.